Health Education for discharge from Pediatric and Neonatal Intensive Care Units - Ricci, Tatiana Souza de Castro Silva (2024)
With these advances in Intensive Care Medicine, there has been an increase in the survival of these children with some special need due the hospitalization or their own pathology. The principles of the Health Unic System and the national humanization policy ame to propose strategies to improve care for these patients, such as health education with parents and family. Therefore, this paper aimed to analyze the main strategies used in the Health Education process Aiming at Hospital Discharge in PICU and NICU environments and their contributions. The Integrative Review was composed of six steps: 1) elaboration of the research question: What are the main strategies used in the Health Education Process Aiming at Hospital Discharge in the PICU and NICU Environments and their contributions? 2) definition of databases (LILACS, MEDLINE, CINAHL, Web of Science, Scopus and SciELO), using the descriptors “Health Education,” “Patient Discharge,” “Neonatal Intensive Care Units” and “Therapy Units”. Pediatric Intensive Care”. Of the 22 comprised the final sample after applying the inclusion and exclusion criteria 3) collected the information to answer the objective; 4) evaluation of selected articles; 5) Interpretation of results as evidence: The prevalence of studies was conducted in the USA and participants were parents and health professionals, there was a gap of 15 years between the first study and the second, the place of greatest research was in the NICU and most studies belonged to the evidence’s level IV. and 6) presentation of the synthesis of the knowledge that had as conclusion: the lack of higher levels of evidence’ studies in the health area in relation to this theme, that the other categories that compose the multidisciplinary team should carry out more research with this approach and in relation to the research field, it is necessary to sensitize other countries and PICU teams to use this practice and publish their results.